Practical means of applying the TRIPS Agreement's flexibilities to spur vaccine production - Andrew D. Mitchell; Antony Taubman (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2023)
Timely and equitable access to vaccines and other health technologies is vital in effectively responding to pandemics and treating other communicable diseases. This paper shows how countries might overcome real or purported intellectual property (IP) barriers to regional COVID-19 vaccine production. In particular, it examines how countries can utilise IP flexibilities to increase and diversify the manufacture and distribution of COVID-19 vaccines. It provides concrete examples of how these flexibilities are practised in various domestic jurisdictions in Asia and the Pacific and sets out practical recommendations for different policy areas.
Keywords: F13; O34; 330; COVID-19; vaccines; intellectual property rights; regional cooperation; Asia-Pacific